2021
DOI: 10.2217/fca-2020-0235
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 24-hour Ambulatory Blood Pressure Monitoring in a COVID-19 Survivor

Abstract: COVID-19 infection primarily causes severe pneumonia complicated by acute respiratory distress syndrome and multiorgan failure requiring a ventilator support. We present a case of a 55-year-old male, admitted with COVID-19. He was obese but had no other medical conditions. His blood pressure was measured by his general physician on several occasions in the past, all values being normal (<140/90 mmHg). He developed multiorgan failure, requiring vasopressor and ventilator support for 17 days. A prone position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
0
11
1
1
Order By: Relevance
“…91 The most frequent arrhythmia in patients with COVID-19 is sinus tachycardia-a homeostatic response to any infection or inflammatory response whose mechanism is, however, not fully understoodthough atrial fibrillation and ventricular tachycardia are also observed. [93][94][95] Among the mechanisms causing this condition, electrolyte imbalance, lung damage, drug side effects and cell signaling cascades after viral infection stands out. 75 In addition, hypoxia due to ARDS is correlated with an increased risk of arrhythmia.…”
Section: Cardiac Pathophysiologymentioning
confidence: 99%
“…91 The most frequent arrhythmia in patients with COVID-19 is sinus tachycardia-a homeostatic response to any infection or inflammatory response whose mechanism is, however, not fully understoodthough atrial fibrillation and ventricular tachycardia are also observed. [93][94][95] Among the mechanisms causing this condition, electrolyte imbalance, lung damage, drug side effects and cell signaling cascades after viral infection stands out. 75 In addition, hypoxia due to ARDS is correlated with an increased risk of arrhythmia.…”
Section: Cardiac Pathophysiologymentioning
confidence: 99%
“…Heart rate tends to be higher in survivors of COVID-19, and our study results differ from literature data. The difference in clinical variables such as sympathetic system activation and cytokine storm may have caused this difference [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many other mechanisms may also explain a persistent elevated heart rate and blood pressure in COVID-19 patients, such as activation of the renin–angiotensin–aldosterone system and sympathetic system, endothelial dysfunction, vasculitis, ischemia, hyperreninemia secondary to volume overload and intravenous saline use, vasopressors use, and mechanical ventilation. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Many other mechanisms may also explain a persistent elevated heart rate and blood pressure in COVID-19 patients, such as activation of the renin-angiotensin-aldosterone system and sympathetic system, endothelial dysfunction, vasculitis, ischemia, hyperreninemia secondary to volume overload and intravenous saline use, vasopressors use, and mechanical ventilation. 25,26 This retrospective study explored the significance of sinus tachycardia on the clinical course of patients with mild COVID-19 infection, who did not require oxygen support or HD/ICU admission. Cohort analysis of sinus tachycardia demonstrated statistical significance for sinus tachycardia to increased CRP, abnormal CXR findings and prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 99%